Four kingdom motifs before and beyond the book of Daniel - Perrin, Andrew B.; Stuckenbruck, Loren T. (Themes in biblical narrative, 2021)
The four kingdoms motif enabled writers of various cultures, times, and places, to periodize history as the staged succession of empires barrelling towards an utopian age. The motif provided order to lived experiences under empire (the present), in view of ancestral traditions and cultural heritage (the past), and inspired outlooks assuring hope, deliverance, and restoration (the future). Four Kingdoms Motifs Before and Beyond the Book of Daniel includes thirteen essays that explore the reach and redeployment of the motif in classical and ancient Near Eastern writings, Jewish and Christian scriptures, texts among the Dead Sea Scrolls, Apocrypha and pseudepigrapha, depictions in European architecture and cartography, as well as patristic, rabbinic, Islamic, and African writings from antiquity through the Mediaeval eras